Analytical approach for calculation of aperture efficiency enhancement of horn antennas using a thin metal cylinder - Ordek, Sezgin; Kizilay, Ahmet (WILEY, 2023)
This study aims to increase horn antenna gain and aperture efficiency in a way that are compatible with aperture electric field distribution similar to TE10 rectangular waveguide mode using analytical calculation method. The proposed analytical approach can be useful to calculate the performance of a horn antenna design with thin (r <
Keywords: aperture efficiency improving; electromagnetic scattering; gain enhancement; horn antenna; DESIGN; Engineering; Optics